Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 283 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Hesperiidae", "TaxonKey is Pieridae", "TaxonKey is Lycaeidae", "TaxonKey is Papilionidae", "TaxonKey is Nymphalidae" ] }, "Country is Denmark", "EventDate 1990-01-01-1993-12-31" ] } The dataset includes 283 records from 2 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0013540-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences